PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (STUDI KASUS RUMAH MAKAN MAMI LAMPUNG) - Mustofa, Ahmad; Azizah, Ana Chosiatul; F Sanjaya, Vicky (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
This research aims to determine the influence of service quality, namely: Physical evidence (tangibles);Reliability (reliability); Responsiveness (responsiveness); Guarantee (assurance); Empathy, as well as theinfluence of product quality, namely: 1) Performance is related to the basic operating characteristics of aproduct. 2) Durability on customer satisfaction at the Mami Lampung restaurant with a sample of 93 customers.The sample was carried out by collecting data through a questionnaire. Data analysis uses PLS analysis whichshows the results that service quality and product quality have a positive and significant effect on customersatisfaction. Keywords : Service Quality; Product Quality; Customer Satisfaction; Restaurant